2016
DOI: 10.1007/s00247-016-3668-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy compared to single-energy CT in pediatric imaging: a phantom study for DECT clinical guidance

Abstract: Dual-energy CT is dose-neutral in imaging the head and abdomen in children. It is not dose-neutral in chest imaging of very small children. With a better understanding of the dose consequences of converting single-energy protocols to dual-energy protocols we can begin to implement clinical dual-energy CT and utilize its unique capabilities in pediatric imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…However, the doses used in dual-energy CT are typically comparable to single-energy CT, if not lower, demonstrating that image quality can be maintained without a dose penalty. 58,[154][155][156][157] It is also important in multienergy CT to consider limitations of the technology being used. This is particularly important with regard to the low-energy dataset, as this is where noise is most prominent, artifacts are more likely to be induced, and quantification accuracy is most limited.…”
Section: C2 Metal Artifact Reductionmentioning
confidence: 99%
“…However, the doses used in dual-energy CT are typically comparable to single-energy CT, if not lower, demonstrating that image quality can be maintained without a dose penalty. 58,[154][155][156][157] It is also important in multienergy CT to consider limitations of the technology being used. This is particularly important with regard to the low-energy dataset, as this is where noise is most prominent, artifacts are more likely to be induced, and quantification accuracy is most limited.…”
Section: C2 Metal Artifact Reductionmentioning
confidence: 99%
“…22 In the chest, the investigators found a small increase in dose with DECT of up to 20% in very small children compared with SECT. 22 Another study of radiation dose for pediatric thoracic, abdominal-pelvic, or CT angiography performed using a dual-source DECT scanner compared the DECT dose to prescanning estimates, if the patient had undergone scanning in SECT mode. 23 The authors concluded that pediatric body DECT scans can be performed at a comparable or less radiation exposure compared with SECT while preserving image quality and contrast.…”
Section: Implementation Of Dect In the Clinical Setting: Radiation Domentioning
confidence: 96%
“…One study evaluated pediatric-size anthropomorphic phantoms using a dual-source DECT scanner. 22 The investiga-tors found that for a similar image quality, DECT was dose neutral for the imaging of the head and abdomen when compared with SECT. 22 In the chest, the investigators found a small increase in dose with DECT of up to 20% in very small children compared with SECT.…”
Section: Implementation Of Dect In the Clinical Setting: Radiation Domentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in technology the radiation dose has lowered and is now comparable to, or even less than, conventional SECT scanners. Either by direct lowering of the dose or the potential of replacing the nonenhanced scan by VNC images and therefore indirect dose reduction [10, 23, 24]. This opens up the wider use of DECT in clinical applications.…”
Section: Dect Techniquementioning
confidence: 99%